2022
DOI: 10.3389/fmicb.2022.840098
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria as Candidates to Support Mars Colonization: Growth and Biofertilization Potential Using Mars Regolith as a Resource

Abstract: Cyanobacteria are indicated as organisms that can possibly support Mars colonization, contributing to the production of oxygen and other commodities therein. In this general context, the aim of this work was to evaluate the ability of three species of cyanobacteria (Anabaena cylindrica, Nostoc muscorum, and Arthrospira platensis) and a green microalga (Chlorella vulgaris) to grow using only the resources existing in Mars, i.e., water and Martian regolith stimulant (MGS-1), under an Earth-like atmosphere. A Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…PCC 7938 demonstrated lower productivity compared to the control cultivated in BG11 medium (approximately 50% less). Similarly, Macario et al [41] reported an increase in optical density when species were cultivated in synthetic media. N. muscorum and A. cylindrica demonstrated their ability to survive when cultivated in an extract of Martian regolith, albeit with a lower biomass yield compared to growth in the standard medium.…”
Section: Introductionmentioning
confidence: 86%
“…PCC 7938 demonstrated lower productivity compared to the control cultivated in BG11 medium (approximately 50% less). Similarly, Macario et al [41] reported an increase in optical density when species were cultivated in synthetic media. N. muscorum and A. cylindrica demonstrated their ability to survive when cultivated in an extract of Martian regolith, albeit with a lower biomass yield compared to growth in the standard medium.…”
Section: Introductionmentioning
confidence: 86%
“…Since the Martian simulant MGS-1 is an aluminosilicate, a similar strong peak to that of metakaolin is observed at a wavenumber of 1008 cm −1 . The absorption at this wavenumber can be assigned to Si-O-Al asymmetric stretching vibrations within the TO4 tetrahedra typical of amorphous aluminosilicates [40]. The adsorption band at 1623 cm −1 is attributed to the bending vibrations of H-O-H [41].…”
Section: Precursors: Mgs-1 and Metakaolinmentioning
confidence: 91%
“…However, most plants and microorganisms are unable to exploit Martian resources, and sending substrates from Earth to Mars to support their metabolism is costly, so the best solution is in-situ utilization of Mars resources. Macário et al (2022) found that the ability of Nostoc sp. to utilize martian regolith simulant is higher than that of other cyanobacteria.…”
Section: Asa-gsh Cycle Protected Nostoc Sp From the Damage Of Mars-li...mentioning
confidence: 99%